Nivel de conocimiento sobre hipertensión arterial en pacientes hipertensos adultos - Pastor Mendoza, Henry Johaun (2020)
Objective: To evaluate the level of knowledge about hypertension in adult hypertensive patients. Material and methods: Prospective, cross-sectional descriptive study, where 100 hypertensive patients attended in the External Consultation Service of Internal Medicine of the Bethlehem Hospital of Trujillo were surveyed. The survey consisted of 3 parts: Sociodemographic characteristics (age, gender, origin, educational level), time of illness and knowledge about arterial hypertension; the latter was considered adequate if they answered correctly of 14-20 questions, and inadequate when they were correct less than 14. The variables under study were compared using the Chi square test with a level of significance of 95%. Results: It was found that the majority of patients corresponded to the female sex (62%), age over 60 years (62%), origin of an urban area (53%), studies up to secondary (42%) and a time of illness of 1-5 years (33%). In addition, 83% had an adequate level of knowledge, with a statistically significant association for sex (p = 0.013) and age (p = 0.041). Conclusion: There is a statistically significant association between the level of knowledge about arterial hypertension and the variables of sex and age.